The addition of clomiphene citrate to ovarian stimulation protocols for poor responders. (August 2020) - Triantafyllidou, Olga; Sigalos, Giorgos; Gkoles, Laertis; Kastora, Stavroula; Vakas, Panagiotis; Batsiou, Eugenia; Vlahos, Nikos
Abstract: Poor ovarian response (POR) is one of the most challenging problems in assisted reproduction. Several strategies have been used to improve pregnancy rates. The use of Clomiphene Citrate (CC) has been shown to improve ovarian stimulation outcomes and decrease gonadotropin requirements in women of advanced reproductive age. However, the combination of CC and gonadotropins to improve pregnancy rates after in IVF in poor responders is still unexplored due to the small number of trials with few participants. This is a prospective cohort trial involving 12 patients diagnosed with poor ovarian response who underwent ovarian stimulation during the period between June 2015 and September of 2017. All patients were treated with the maximum dose of gonadotropins (hMG, 300 IU/day, hMG group) according to a short gonadotropin/GnRH antagonist protocol. In a subsequent cycle those patients underwent the same stimulation protocol with the addition of 100 mg of CC from day 3 to day 7 (CC-hMG group). Supplementation with 100 mg of CC resulted in a statistically significant increase in estradiol levels, number of follicles and number of oocytes retrieved, as well as an increase in the number of total embryos available for transfer. Furthermore, a significant reduction was observed in cancellation rates in the CC-hMG group. Two clinical pregnancies, which resulted in two live births and 3 biochemical pregnancies were achieved in the CC/hMG group. Furthermore, by employing open-source, biological data we identified a common gene (Estrogen Receptor 1, ESR1) between genetic targets of clomiphene treatment and POR which could explain the benefits of clomiphene in this group of patients. In conclusion, the addition of CC 100 mg to the stimulation regimen in women diagnosed with POR and previous failed IVF cycles could improve stimulation results, but this study could not demonstrate any benefit in terms of clinical pregnancies and live births. The effectiveness of this treatment requires further investigation.